You are on page 1of 18

# Chapter 1 Homework Solutions

## Timothy R. Tuinstra, Ph.D.

November 2, 2010
1.1-3
a) Find the energies of the pair of signals x(t) and y(t) depicted in the gure.
b) Sketch and nd the energies of signals x(t) + y(t) and x(t) y(t). Can you
make any observation from these results?
For Fig. P1.1-3 (a)
Energy of x(t):
E
x
=

2
0
x
2
(t)dt
=

2
0
dt
= 2
Energy of y(t):
E
y
=

2
0
y
2
(t)dt
=

1
0
dt +

2
1
dt
= 2
For Fig. P1.1-3 (b)
Energy of x(t):
E
x
=

2
0
x
2
(t)dt
=

0
dt +

dt
= 2
Energy of y(t):
E
y
=

2
0
y
2
(t)dt
= 2
1
For Fig. P1.1-3 (c)
Energy of x(t):
E
x
=

0
x
2
(t)dt
=

0
dt
=
Energy of y(t):
E
y
=

0
y
2
(t)dt
=
Part b)
The energy of x(t) +y(t):
E =

2
0
(x(t) +y(t))
2
dt
=

1
0
4dt
= 4
2
The energy of x(t) y(t):
E =

2
0
(x(t) y(t))
2
dt
=

2
1
4dt
= 4
The energy of x(t) +y(t):
E =

2
0
(x(t) +y(t))
2
dt
=

2
0
4dt +

2
3
2
4dt
= 4
The energy of x(t) y(t):
E =

2
0
(x(t) y(t))
2
dt
=
3
2

2
4dt
= 4
3
The energy of x(t) +y(t):
E =

0
(x(t) +y(t))
2
dt
=

4
0
4dt
=
The energy of x(t) y(t):
E =

0
(x(t) y(t))
2
dt
=

4
4dt
= 3
4
1.1-6 Determine the power and the RMS value for each of the following
signals:
a) x(t) = 10 cos(100t +
pi
3
)
The frequency of x(t) is f =
100
2
=
50

## which implies that the period is

T =

50
seconds.
P
x
=
1
T

T
x
2
(t)dt
= 100
50

50
0
cos
2
(100t +

3
)dt
= 100
50

50
0
cos
2
(100t)dt
= 100
50

50
0
(
1
2
+
1
2
cos(200t))dt
=
5000

50
1
2
= 50
The RMS value is found by computing the root of the power P
x
:

50
b) x(t) = 10 cos(100t +

3
) + 16 sin(150t +

5
)
In this case there are two sinusoids, and the power is found by computing the
power of each sinusoid and adding. Also, the phase is irrelevant when computing
power. Therefore
P
x
= 100
1
T
1

T1
cos
2
(100t)dt + 256
1
T
2

T2
sin
2
(150t)dt
= 100
1
T
1

T1
(
1
2
+
1
2
cos(200t))dt + 256
1
T
2

T2
(
1
2

1
2
sin(300t))dt
= 50 + 128
= 178
The RMS value is found by computing the root of the average power:

178
c) x(t) = (10+2 sin(3t)) cos(10t) Here, we make use of trig identities to make
our work simpler. To do that we realize that
sin() cos() =
1
2
(sin( ) + sin( +))
So now x(t) is
x(t) = 10 cos(10t) + (sin(7t) + sin(13t))
5
We have three sinusoids at 3 dierent frequencies so we add their powers.
By now it should be obvious that the power of each sinusoid is simply half the
value of the square of their amplitude:
P
x
=
10
2
2
+
1
2
+
1
2
= 51
The RMS value is

51
d) x(t) = 10 cos(5t) cos(10t)
Again, we make use of a trig identity:
x(t) = 10
1
2
(cos(5t) + cos(15t))
And the power is
P
x
=
25
2
+
25
2
= 25
The RMS value is

25 = 5
e) x(t) = 10 sin(5t) cos(10t) = 10
1
2
(sin(5t) + cos(15t))
The power is then easily calculated:
P
x
= 25
the RMS value is

25 = 5
f) x(t) = e
jt
cos(
0
t)
This happens to be a complex signals and the approach is a little dierent.
For calculating the power of complex signals we use the following formula:
P
x
=
1
T

T
|x(t)|
2
dt
where |x(t)|
2
= x(t)x (t).
So we have:
P
x
=
1
T

T
e
jt
e
jt
cos
2
(
0
t)dt
=
1
T

T
cos
2
(
0
t)dt
=
1
2
And the RMS value is
1

2
6
For the signal f(t) shown, sketch each of the following:
a) f(t 4)
b) f(
t
1.5
)
7
c) f(t)
d) f(2t 4)
8
e) f(2 t)
9
1.4-2 Express each of the signals shown by a single expression valid for all t.
a)
f
1
(t) = (4t + 4)(u(t + 1) u(t)) + (2t + 4)(u(t) u(t 2))
b)
f
2
(t) = t
2
(u(t) u(t 2)) + (2t 8)(u(t 2) u(t 4))
10
1.4-5 Evaluate the following integrals: The key to this problem is to use the
sifting property of the Dirac Delta Function.
a)

()f(t )d = f(t )|
=0
= f(t)
b)

f()(t )d = f()|
=t
= f(t)
c)

(t)e
jt
dt = e
jt
|
t=0
= 1
d)

(t 2) sin(t)dt = sin(t)|
t=2
= 0
e)

(t + 3)e
t
dt = e
t
|
t=3
= e
3
f)

(t
3
+ 4)(1 t)dt = (t
3
+ 4)|
t=1
= 5
g)

## f(2 t)(3 t)dt = f(2 t)|

t=3
= f(1)
h)

e
x1
cos

2
(x 5)

(x 3)dx = e
x1
cos

2
(x 5)

|
x=3
= e
2
11
1.7-1 For the systems described by the equations below, with the input
f(t) and output y(t), determine which of the systems are linear and which are
nonlinear.
a)
y + 2y = f
2
Check to see what happens if f
1
y
1
and f
2
y
2
:
y
1
+ 2y
1
= f
2
1
y
2
+ 2y
2
= f
2
2
Now see what happens if we put in f
1
+f
2
into the system:
RHS:
(f
1
+f
2
)
2
= f
2
1
+ 2f
1
f
2
+f
2
2
= y
1
+ 2y
1
+ y
2
+ 2y
2
+ 2f
1
f
2
=
d
dt
(y
1
+y
2
) + 2(y
1
+y
2
) + 2f
1
f
2
.
This is not the same system as above and so the system is nonlinear.
b)
y + 3ty = t
2
f
Assume that f
1
y
1
and f
2
y
2
.
y
1
+ 3ty
1
= t
2
f
1
y
2
+ 3ty
2
= t
2
f
2
Now see what happens if we put in f
1
+f
2
into the system:
RHS:
t
2
(f
1
+f
2
) = t
2
f
1
+t
2
f
2
= y
1
+ 3ty
1
+ y
2
+ 3ty
2
d
dt
(y
1
+y
2
) + 3t(y
1
+y
2
)
This system matches what is given above, so this system is Linear.
c)
( y)
2
+ 2y = f
12
Assume that f
1
y
1
and f
2
y
2
.
( y
1
)
2
+ 2y
1
= f
1
( y
2
)
2
+ 2y
2
= f
2
Now see what happens if we put in f
1
+f
2
into the system:
f
1
+f
2
= ( y
1
)
2
+ 2y
1
+ ( y
2
)
2
+ 2y
2
= ( y
1
)
2
+ ( y
2
)
2
+ 2(y
1
+y
2
)
= ( y
1
+ y
2
)
2
+ 2(y
1
+y
2
)
This system is Nonlinear
d)
y +y
2
= f
Assume that f
1
y
1
and f
2
y
2
.
y
1
+y
2
1
= f
1
y
2
+y
2
2
= f
2
Now see what happens if we put in f
1
+f
2
into the system:
f
1
+f
2
= y
1
+ y
2
+y
2
1
+y
2
2
=
d
dt
(y
1
+y
2
) +y
2
1
+y
2
2
=
d
dt
(y
1
+y
2
) + (y
1
+y
2
)
2
This system is Nonlinear
e)
3y + 2 = f
Assume that f
1
y
1
and f
2
y
2
.
3y
1
+ 2 = f
1
3y
2
+ 2 = f
2
Now see what happens if we put in f
1
+f
2
into the system:
f
1
+f
2
= 3y
1
+ 3y
2
+ 2 + 2
= 3(y
1
+y
2
) + 4
= 3(y
1
+y
2
) + 2
13
This system is Nonlinear
f)
y + (sin(t))y =

f + 2f
Assume that f
1
y
1
and f
2
y
2
.
y
1
+ (sin(t))y
1
=

f
1
+ 2f
1
y
2
+ (sin(t))y
2
=

f
2
+ 2f
2
Now see what happens if we put in f
1
+f
2
into the system:
d
dt
(f
1
+f
2
) + 2(f
1
+f
2
) =

f
1
+ 2f
1
+

f
2
+ 2f
2
= y
1
+ (sin(t))y
1
+ y
2
+ (sin(t))y
2
=
d
dt
(y
1
+y
2
) + (sin(t))(y
1
+y
2
)
the system is Linear
g)
y + 2y = f

f
Assume that f
1
y
1
and f
2
y
2
.
y
1
+ 2y
1
= f
1

f
1
y
2
+ 2y
2
= f
2

f
2
Now see what happens if we put in f
1
+f
2
into the system:
(f
1
+f
2
)
d
dt
(f
1
+f
2
) = f
1

f
1
+f
2

f
2
+f
1

f
2
+f
2

f
1
= y
1
+ 2y
1
+ y
2
+ 2y
2
+f
1

f
2
+f
2

f
1
=
d
dt
(y
1
+y
2
) + 2(y
1
+y
2
) +f
1

f
2
+f
2

f
1
=
d
dt
(y
1
+y
2
) + 2(y
1
+y
2
)
this system is Nonlinear
h)
y =

f()d
14
Assume that f
1
y
1
and f
2
y
2
.
y
1
=

f
1
()d
y
2
=

f
2
()d
Now see what happens if we put in f
1
+f
2
into the system:

(f
1
+f
2
)d =

f
1
()d +

f
2
()d
= y
1
+y
2
this system is Linear
15
1.7-2 For the systems described by the equations below, with the input f(t)
and output y(t), determine which of the systems are time-invariant and which
are time-varying systems.
a)
y(t) = f(t 2)
Shift the input and see what happens:
f(t 2) = y(t )
Shifting the input just shifts the output by the same amount. this system is
Time-invariant
b)
y(t) = f(t)
f(t) y(t) = f(t)
Shifting the output:
y(t ) = f((t ))
= f( t)
Now shift the input and see if it is equivalent:
f(t ) f(t )
= f( t)
this system is Not Time-invariant
c)
y(t) = f(at)
f(t) y(t) = f(at) (1)
Shifting the output:
y(t ) = f(a(t ))
= f(at a)
Now shift the input and see if it is equivalent
f(t ) f(at )
= f(at a)
this system is Not Time-Invariant
16
d)
f(t) y(t) = tf(t 2)
Shifting the output:
y(t ) = (t )f(t 2)
Now shift the input and see if we achieve the same result:
f(t ) tf(t 2)
= (t )f(t 2)
this system is Not Time-Invariant
e)
f(t) y(t) =

5
5
f()d
Shifting the output:
y(t ) =

5
5
f()d
Now shift the input and see if we achieve the same result:
f(t )

5
5
f( )d
=

5
5
f()d
this system is Not Time-Invariant
f)
f(t) y(t) =

df
dt

2
Now shift the output:
y(t ) =

d
dt
f(t )

2
Now shift the input and see if they are equivalent:
f(t )

d
dt
f(t )

2
this system is Time-Invariant
17
1.8-3 Water ows into a tank at a rate of q
i
units/s and ows out through
the outow valve at a rate of q
0
units/s. Determine the equation relating the
outow q
0
to the input q
i
. The outow rate is proportional to the head h.
Thus q
0
= Rh where R is the valve resistance. Determine also the dierential
equation relating the head h to the input q
i
.
Hint: The net inow of water in time t is (q
i
q
0
)t. This inow is also
Ah where A is the cross section of the tank.
The key thing here is to determine what physical laws govern this system.
Clearly, the inow rate of water has to equal the rate that water is leaving the
tank plus the rate at which the tank is lling up. Lets try writing this as an
equation:
(q
i
q
0
)t = Ah
Dividing through by t and taking the limit as t 0 gives
q
i
q
0
= A

h
=
A
R
q
0
Rearranging this into the normal form of a dierential equation gives:
q
0
+
R
A
q
0
=
R
A
q
i
Finally to get D.E. relating h and q
i
, we write
q
i
Rh = A

h
and rearranging gives:

h +
R
A
h =
q
i
A
18